2016
DOI: 10.1007/s11192-016-2004-4
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of micro/nano-bubble related research: current trends, present application, and future prospects

Abstract: With great versatile characteristics, micro/nano-bubble related research have attracted much attention due to their extensive applications in the last half century.Researchers not merely focus on their physi-chemical properties, but also aim at their wellcontrolled generation methods and potential adhibition field. It can be expected that the future prospects of micro/nano-bubble related research will be tremendous and that there will be even more to be explored. In this case study, a bibliometric analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 74 publications
3
15
0
Order By: Relevance
“…In the same way, the majority of top-10 authors were from United States or Australia. As found in other research areas, collaborative regions, institutions and authors ten to be geographically correlated [44]. Moreover, the results of co-citation analysis of highly-cited authors showed clearly four distinct clusters, which represented a subfield of this research area.…”
Section: Discussionsupporting
confidence: 66%
“…In the same way, the majority of top-10 authors were from United States or Australia. As found in other research areas, collaborative regions, institutions and authors ten to be geographically correlated [44]. Moreover, the results of co-citation analysis of highly-cited authors showed clearly four distinct clusters, which represented a subfield of this research area.…”
Section: Discussionsupporting
confidence: 66%
“…The order of document types was similar to previous scientometric research in other research areas. 21,22 Compared with other document types, articles could better reect the progress of the biochar area, and it was also the dominant type of these 18 908 publications; therefore, the following analysis is based on articles only.…”
Section: Document Typesmentioning
confidence: 99%
“…7: 297-302 Feng et al 2009) and so on. Currently, the study of oxygen micro-nano bubble enhancement in water purification and medical care is more (Yoshida et al 2008, Zheng et al 2016. However, there are few studies on micro-nano bubble aeration in agricultural irrigation, especially in rice irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…It has many advantages, such as long time (Ohgaki et al 2010), large surface area (Tasaki et al 2009), strong adsorbability (Bunkin et al 2012), good stability (Feng et al 2009) and so on. Currently, the study of oxygen micro-nano bubble enhancement in water purification and medical care is more (Yoshida et al 2008, Zheng et al 2016. However, there are few studies on micro-nano bubble aeration in agricultural irrigation, especially in rice irrigation.…”
mentioning
confidence: 99%